Investigation of Foraging Behavior and Food Detection in the Freshwater Snail: Rivomarginella morrisoni (Gastropoda, Marginellidae) - A Laboratory Case Study - Navapong Subpayakom; Pongrat Dumrongrojwattana; Supattra Poeiam (My University, 2025)
This study investigates the foraging behavior and food detection mechanisms of Rivomarginella morrisoni , a freshwater snail endemic to Thailand. Snails from four river basins in Central Thailand were observed under controlled conditions to assess daily activity patterns, food preferences, sensory reliance, and the effects of light and darkness on locomotion. Results revealed nocturnal foraging behavior, a strong preference for shrimp over fish and marsh snails, and greater consumption of aged shrimp than fresh or decayed shrimp. Light and darkness preference experiments revealed no significant effect on locomotion behavior, while chemosensory tests confirmed attraction to food-related chemical cues. Visual detection played a minimal role. These findings highlight the species' reliance on chemosensory cues and provide a foundation for future ecological and conservation research.
Keywords: Aquatic Invertebrate Ecology and Behavior